การแสดงออกของเฮพพาแรนเนสในเนื้อเยื่อมะเร็งช่องปาก - สุภมาส แก้วกระแสสินธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purpose of this study was to determine the levels of heparanase m-RNA in oral squamous cell carcinoma (OSCC) and adjacent histological normal squamous tissues. Tissues from 18 OSCC patients were dissected and immersed immediatedly in liquid nitrogen after the operation. Total RNA was extracted from the tissues by guanidine isothiocyanate-phenol and chloroform. The quantity and quality of total RNA was checked using spectrophotometer and formaldehyde agarose gel electrophoresis, respectively. Reverse transcription was employed to produce cDNA and then PCR was performed by conventional method as well as real time PCR. Both methods showed similar results that the expression levels of heparanase from both tissues were not significantly different (p>0.05). Therefore, it seemed that there was no relationship between heparanase expression and oral squamous cell carcinoma.